Analisis Risiko Keterlambatan Proyek Pada Pembangunan Revitalisasi Gedung Pasar Rakyat Leles Garut Tahap III - Indriani Isabela; Ganjar J Johari (International Forum of Researchers and Lecturers, 2023)
The Revitalization Development of the Leles People's Market Building Phase III is a government development project overseen by the Garut Regency DISPERINDAG. The construction of this market building began in mid-2021 and was planned to be completed within 120 days of the project plan, however, there were obstacles that resulted in the realization of the construction process requiring additional time to complete the construction. The method used in this study is the Fault Tree Analysis (FTA) method, the purpose of which is to find the fault tree of various errors that will result in the occurrence of unwanted events and the Event Tree Analysis (ETA) method is used to estimate and assess the probability of each consequence. can arise from an event in anticipation of its various consequences. This research methodology uses the concepts used in the survey using questionnaires and interviews with informants/respondents involved in the Catfish Market Revitalization project. There are two main intermediate events that cause delays in the development of the Revitalization of the Leles Garut People's Market, namely structural work / architectural work and work on the completion of side buildings. The result of identifying the total value of the minimum cut set combination probability for the Top Event of 0.9998 is the overall result of the total combination calculation of the minimum cut set. The results of the Initiating scenario impact analysis which has a